2012
DOI: 10.1007/s00396-012-2618-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of micron-sized polymeric particles in soap-free emulsion polymerization using oil-soluble initiators and electrolytes

Abstract: Soap-free emulsion polymerization of styrene using oil-soluble initiators and electrolytes was investigated to synthesize micron-sized polystyrene particles. It was clear that an oil-soluble initiator, such as AIBN, worked like a water-soluble initiator in soap-free emulsion polymerization of styrene to prepare monodispersed particles with negative charges, probably because of the polarization of the electron-attractive functional groups decomposed from the initiators and the pi electron cloud of benzene in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 21 publications
3
20
0
Order By: Relevance
“…The size and number of styrene droplets decreased with increasing polymerization time; eventually, the droplets became invisible from the optical microscopy observation (Figure S5, Supporting Information). After the synthesis, 230 nm PS spherical particles were produced (Figure S6, Supporting Information), as reported elsewhere …”
Section: Resultsmentioning
confidence: 99%
“…The size and number of styrene droplets decreased with increasing polymerization time; eventually, the droplets became invisible from the optical microscopy observation (Figure S5, Supporting Information). After the synthesis, 230 nm PS spherical particles were produced (Figure S6, Supporting Information), as reported elsewhere …”
Section: Resultsmentioning
confidence: 99%
“…The monodispersed particles with a diameter of 340 nm and a zeta potential of -44.8 mV were prepared as shown in Fig. 8a and Table 4 (Yamamoto T., 2012). The surface potential was so negative that the polystyrene particles showed good dispersion stability after the polymerization.…”
Section: Sfep Of Aromatic Vinyl Monomer Using Aibnmentioning
confidence: 99%
“…Telford et al also prepared polymer particles based on the particle coagulation mechanism [15][16][17]. As mentioned by Koper et al, Yamamoto et al reported that the addition of electrolyte effectively promotes hetero-coagulation and prevents secondary nucleation [18].…”
Section: Introductionmentioning
confidence: 96%